Pemikiran Dakwah Dr. (Hc). Kh. Ez. Muttaqien Tentang Politik, Sosial Ekonomi, dan Pendidikan - Ridfiazhi Aldreka; Rahmat Effendi (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Advocacy is the duty of each individual according to his abilities as stated in QS. 16:125 The preachers transmit in various ways and means in various fields. They convey messages and explanations for their calling and inviting the community through their speech, writing or actions that can be done individually, in groups or through organizations/institutions, and Dr (HC). KH. EZ. Al-Muttaqin is an example of the influential preachers of his time. The book